The complete plastome of Nannoglottis ravida, an extremely endangered species in the Qinghai-Tibet Plateau - Yang, Bibo (Mitochondrial DNA B Resour, 2020)
Nannoglottis ravida is an extremely endangered species in the Qinghai-Tibet Plateau. Based on the second-generation high-throughput genome sequencing, we assembled the plastome of this species. The length of the total plastome is 152,324 bp with a typical quadripartite structure including a large single-copy region of 83,708 bp, a small single-copy region of 29,882 bp and two reverse repeat regions of 19,367 bp respectively. A total of 131 genes were annotated including 85 protein-coding genes (PCG), 36 tRNA genes, 8 rRNA genes and 2 pseudogenes. The constructed phylogenetic tree with other species of two tribes Senecioneae and Astereae based on plastomes suggests that N. ravida has a close relationship with the Astereae, but diverged early from this tribe.